Strategies to Reduce Barriers to Recruitment and Participation - Margaret Pribulick; Ishan Canty Williams; Pamela Stewart Fahs (Rural Nurse Organization; Binghamton University, 2012)
Purpose To identify barriers encountered and solutions employed to improve research recruitment and retention of rural subjects for participation in the Promoting Heart Health in Rural Women (PHH) study. Methods This article provides an examination of experiences encountered by nurse researchers in recruiting rural women from two locations to a randomized, controlled trial. Problem solving through broadening recruitment areas and inclusion criteria, community liaison assistance, identification of rural-specific strategies in the literature, and perseverance helped to overcome barriers to subject recruitment and retention in this rural Phase-II nurse-run intervention study. Clinical Relevance Research studies need to be conducted in order to build a body of evidence for nursing interventions to reduce cardiovascular disease risk factors in rural women. A study is strengthened by a robust sample that provides power to statistical analysis. Without discussion of real-world experiences and appropriate and effective recruitment and retention strategies in nursing research, there is little chance of conducting research with appropriate power to build evidence-based practice.